The Influence of The Environmental Approach on Five-Grade Students’ Critical Thinking Ability - Reza Maida Nur Afana; Jupriyanto Jupriyanto; Yunita Sari (Universitas Negeri Semarang, 2023)
This study focuses on the influence of learning approaches on students' critical thinking skills, the lack of teacher diversity in teaching, and the utilization of learning media sources. After applying the environmental approach, the purpose was to determine the effect of critical thinking skills and minimum completeness criteria (KKM). The research design is Quasi-Experimental Design (Time Series Design). The research sample was 20 fifth-grade students at SDN Gondo 01. The pretest and posttest normality tests were normally distributed. Output SPSS pretest column sig. has a value of 0.200 > (0.05) means that the data is normally distributed. The posttest results of the SPSS output are in the sig column. The value 0.155 > (0.05) means the data is normally distributed. The paired sample t-test hypothesis test obtained sig. (2-heads) 0.000. If sig. (2-tailed) 0.000 < (0.05), then Ha is accepted, meaning that there is an influence of the environmental approach on students' critical thinking skills. The results of hypothesis testing two t-tests for one Sample obtained the results of Tcount (0.20) and Ttable (2.09). If Tcount > - Ttable, then Ho is accepted, which means that the student has fulfilled the KKM, which is 70. Key words: Environmental Approach, Critical Thinking, Science Learning.